2014
DOI: 10.1016/j.peptides.2014.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Arginine-rich, cell penetrating peptide–anti-microRNA complexes decrease glioblastoma migration potential

Abstract: MicroRNAs (miRNAs) are a class of gene regulators originating from non-coding endogenous RNAs. Altered expression, both up - and down-regulation, of miRNAs plays important roles in many human diseases. Correcting miRNA dysregulation by either inhibiting or restoring miRNA function may provide therapeutic benefit. However, efficient, nontoxic miRNA delivery systems are in need. Cell penetrating peptides (CPPs) have been widely exploited for protein, DNA, and RNA delivery. Few have examined CPP transfection effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…GFP siRNA complexed to 9DR or 9LR did not silence GFP expression in Neuro2a cells stably expressing the protein (Figures 1G and 1H). Therefore, 9R peptides poorly translocated siRNA, unless used at a high molar excess [>50, (Cantini, et al, 2013; Wang, et al, 2007; Zhang, et al, 2014)].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GFP siRNA complexed to 9DR or 9LR did not silence GFP expression in Neuro2a cells stably expressing the protein (Figures 1G and 1H). Therefore, 9R peptides poorly translocated siRNA, unless used at a high molar excess [>50, (Cantini, et al, 2013; Wang, et al, 2007; Zhang, et al, 2014)].…”
Section: Resultsmentioning
confidence: 99%
“…Despite their typical ability to effectively translocate biological macromolecules, R-CPPs are poor vehicles for cytoplasmic delivery of siRNA. For measurable mRNA knockdown, a huge excess of CPP molecules and high siRNA concentrations (above the therapeutic range) and/or association with reagents that disrupt endosomes is generally necessary (Akita, et al, 2010; Cantini, et al, 2013; El-Sayed, et al, 2009; Endoh and Ohtsuki, 2009; Erazo-Oliveras, et al, 2012; Lee, et al, 2008; Margus, et al, 2012; van Asbeck, et al, 2013; Zhang, et al, 2014). Imaging studies reveal the vast majority of CPP-siRNA complexes trapped for extended time periods in intracellular vesicles with little or no cytoplasmic localization (Al-Taei, et al, 2006; El-Sayed, et al, 2009; Erazo-Oliveras, et al, 2012; Fretz, et al, 2007; Fuchs and Raines, 2004; Maiolo, et al, 2005; Verdurmen, et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…With the similar charge and size, the oligoarginine available on the micelle surface was expected to influence the ability of micelles to associate with or enter cells, but the total arginine and surface charge was not directly related to cellular interaction. 24, 40, 41 Only the available arginine content on the micelle surface correlated with the ability of the micelles to interact with cells. This further supports the idea that the oligoarginine on the mPEG-PLA-R 15 micelles was more available for interactions.…”
mentioning
confidence: 99%
“…CPPs are small peptides containing 6–30 amino acids that are capable of membrane translocation and internalization by adsorptive mediated endocytosis [137]. RNA oligonucleotides can form complexes with peptides such as octoarginine (R8) which can aid in their cellular internalization and endosomal escape in comparison to unmodified RNAi molecules [137]. Consequently, CPPs could increase the RNAi therapeutic effect.…”
Section: Assessing Rnai Delivery For Gbm Treatmentmentioning
confidence: 99%
“…Consequently, CPPs could increase the RNAi therapeutic effect. For example, Y. Zhang et al showed that antimir-21/R8 treatment of U251 human GBM cells led to the downregulation of the well-known miR-21-regulated genes, PDCD4 and SERPINB5; as well as inhibition of cell migration by 25% in comparison to the antimir/R8 negative control group [137]. Sariah Khormaee et al evaluated the effect of covalently attaching stathmin-targeted siRNAs to a PP75 cell penetrating peptide [138].…”
Section: Assessing Rnai Delivery For Gbm Treatmentmentioning
confidence: 99%